2013
DOI: 10.21109/kesmas.v7i7.28
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Musical Activities and Cognitive Function of the Elderly

Abstract: Decreasing cognitive function of the elderly is one of the most common problems that might affect their quality of life. Music is an element that is believed to be able to contribute to the quality of life of the elderly. However, whether musical activities that are done throughout the life span related to cognitive function is unclear. In this research, we evaluated the association between lifetime musical activities and cognitive function. Fifty three older adults from three nursing homes in East Jakarta wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(26 reference statements)
0
3
0
1
Order By: Relevance
“…Dalam bidang kesehatan, masalah baru yang seringkali dihadapi ialah berhubungan dengan cara untuk selalu mempertahankan kesehatan dari para lansia sehingga para lansia mampu untuk melanjutkan fungsi kehidupan seperti: mampu beraktifitas fisik, serta mempertahankan fungsi sosial dan fungsi kognitif. 3 Kognitif adalah salah satu fungsi tingkat tinggi otak manusia yang terdiri dari beberapa aspek seperti; persepsi visual dan konstruksi kemampuan berhitung, persepsi dan pengguanan bahasa, pemahaman dan penggunaan bahasa, proses informasi, memori, fungsi eksekutif, dan pemecahan masalah sehingga jika terjadi gangguan fungsi kognitif dalam jangka waktu yang panjang dan tidak dilakukan penanganan yang optimal dapat mengganggu aktifitas sehari-hari. 4 Di kalangan lansia sendiri penurunan fungsi kognitif merupakan penyebab terbesar terjadinya ketergantungan terhadap orang lain untuk merawat diri sendiri akibat ketidakmampuan dalam melakukan aktifitas sehari-hari.…”
unclassified
“…Dalam bidang kesehatan, masalah baru yang seringkali dihadapi ialah berhubungan dengan cara untuk selalu mempertahankan kesehatan dari para lansia sehingga para lansia mampu untuk melanjutkan fungsi kehidupan seperti: mampu beraktifitas fisik, serta mempertahankan fungsi sosial dan fungsi kognitif. 3 Kognitif adalah salah satu fungsi tingkat tinggi otak manusia yang terdiri dari beberapa aspek seperti; persepsi visual dan konstruksi kemampuan berhitung, persepsi dan pengguanan bahasa, pemahaman dan penggunaan bahasa, proses informasi, memori, fungsi eksekutif, dan pemecahan masalah sehingga jika terjadi gangguan fungsi kognitif dalam jangka waktu yang panjang dan tidak dilakukan penanganan yang optimal dapat mengganggu aktifitas sehari-hari. 4 Di kalangan lansia sendiri penurunan fungsi kognitif merupakan penyebab terbesar terjadinya ketergantungan terhadap orang lain untuk merawat diri sendiri akibat ketidakmampuan dalam melakukan aktifitas sehari-hari.…”
unclassified
“…In order to achieve 'optimal aging' , they must be able to continue their life function as well as they can, such as being able to physically, socially and cognitively function. 4 One of the health problems that often arise in the elderly population is the decline in cognitive function. Cognitive function itself is obtained through the interaction between the formal environment of education and non-formal environment that is obtained from everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies examining older adult musicians have not tested a range of cognitive domains (Nevriana, Riono, Rahardjo, & Kusumadjati, 2013), did not study neuropsychological functioning at all but rather dementia diagnosis (Balbag, Pedersen, & Gatz, 2014), or examined musical knowledge and its relationship to semantic and episodic memory (Gooding, Abner, Jicha, Kryscio, & Schmitt, 2013). Nevriana et al (2013) studied correlations on scores of a common cognitive screening measure (MiniMental State Exam, MMSE) of musicians in nursing homes who were involved in music activities and those who were not.…”
Section: Cognitive Differences Between Musicians and Non-musiciansmentioning
confidence: 99%
“…Nevriana et al (2013) studied correlations on scores of a common cognitive screening measure (MiniMental State Exam, MMSE) of musicians in nursing homes who were involved in music activities and those who were not. They found that there was a correlation between MMSE scores and lifetime musical activities.…”
Section: Cognitive Differences Between Musicians and Non-musiciansmentioning
confidence: 99%